Secular trends in height, body mass, and BMI among girls in the Eastern Poland region (1986–2021) - Wasiluk, Agnieszka (Zdravstveno varstvo, 2026)
Introduction To assess long-term changes in body mass index (BMI) and weight status among girls from Eastern Poland between 1986 and 2021. Methods Data were obtained from repeated cross-sectional, population-based surveys conducted in Eastern Poland in 1986, 1996, 2006, 2016, and 2021. The study included 14,825 girls aged 8, 13, and 17 years, recruited from the same schools across survey waves. Body height and body mass were measured by trained personnel using standardised procedures, and BMI was calculated. Weight status categories (underweight, normal weight, overweight and obesity) were defined using international BMI cut-off points. Statistical analyses included analysis of variance and post hoc comparisons. Results Between 1986 and 2021, the largest increase in BMI was observed among 13-year-old girls (+1.66 kg/m2), followed by 8-year-olds (+1.14 kg/m2), while a decrease occurred among 17-year-olds (-1.13 kg/m2). The prevalence of underweight declined among 8- and 13-year-olds by 2.70 and 3.15 percentage points, respectively, but increased among 17-year-olds by 1.85 percentage points. In parallel, the combined prevalence of overweight and obesity increased across all age groups: 19.89 percentage points among 8-year-olds, 10.66 among 13-year-olds, and 3.87 among 17-year-olds, with the greatest increases occurring in recent survey periods. Conclusions Over the past 35 years, BMI distribution among girls in Eastern Poland has shifted towards higher values, accompanied by a rise in overweight and obesity. The increase in underweight among older adolescents may reflect psychosocial pressures. These findings highlight the need for age-specific public health strategies addressing both excessive and insufficient body mass.
Keywords: BMI; nutritional status; physical development; prehranski status; secular trends; sekularni trendi; telesni razvoj